A survey of perioperative complications with Clavien-Dindo classification: a cross-sectional study - Muhammad Talha Khan; Talha Akhtar; Muhammad Atif Yasin; Noman Ahmed Chaudhary; Abdullah Sadiq; Ahsan Tameez ud din (Journal of the Pakistan Medical Association, 2020)
Objectives: To determine the incidence of complications in elective surgeries and to grade them according to the Clavien-Dindo Classification System. Method: The cross-sectional study was conducted in the General Surgery Operation Theatre of Holy Family Hospital, Rawalpindi, Pakistan, from February to April 2018, and comprised patients undergoing elective surgeries. Age, gender, region of surgery, type and grade of complications, were recorded using Clavien-Dindo Classification proforma. Data was analysed using SPSS 23. Results: Of the total 212 patients, 36(16.9%) had some complication. There were significantly more complications in people aged 40 years or above compared to those <40 years (p<0.05). Of the total surgeries, 126(59.43%) were in the abdomino-pelvic region. Conclusion: Peri-operative complications were found to be significantly related with age of the patient and the type of surgery. Key Words: Classification, Peri-operative procedures, Continuous...